Metastatic biomarkers in synovial sarcoma. Issue 1 (December 2017) - de Necochea-Campion, Rosalia; Zuckerman, Lee; Mirshahidi, Hamid; Khosrowpour, Shahrzad; Chen, Chien-Shing; Mirshahidi, Saied
Abstract Synovial sarcoma (SS) is an aggressive soft tissue sarcoma (STS) that typically occurs in the extremities near a joint. Metastatic disease is common and usually occurs in the lungs and lymph nodes. Surgical management is the mainstay of treatment with chemotherapy and radiation typically used as adjuvant treatment. Although chemotherapy has a positive impact on survival, the prognosis is poor if metastatic disease occurs. The biology of sarcoma invasion and metastasis remain poorly understood. Chromosomal translocation with fusion of the SYT and SSX genes has been described and is currently used as a diagnostic marker, although the full impact of the fusion is unknown. Multiple biomarkers have been found to be associated with SS and are currently under investigation regarding their pathways and mechanisms of action. Further research is needed in order to develop better diagnostic screening tools and understanding of tumor behavior. Development of targeted therapies that reduce metastatic events in SS, would dramatically improve patient prognosis.